Psychiatry and mental health in Peru - Delgado, Honorio (1936)
The study of mental disorders and care for those who suffer in our country do not have development corresponding to their importance. There have been, however, laudable efforts and significant achievements, noteworthy for its very rarity. Everything done is located in Lima. So try to psychiatry in Lima is trying to psychiatry in Peru. It should, however, separate and compare the contribution of Capital regarding psychiatric subject, the patient. Accordingly, in this Article, will be the subject of our review, with due brevity: I, the history of our assistance alienated; II, the culture of psychiatry in Peru; III, the population of sick mind from Lima and the rest of the country; IV, mental health in Peru; and V, the situation and the problems that this offers for assistance, and prophylaxis study of psychic disturbances.